Reasons for Hospital Admissions in Chronic Hypercapnic COPD Patients on Long-Term Nocturnal Noninvasive Ventilation – A Prospective Observational Study - Koschel S; Stanzel SB; Kroppen D; Duiverman M; Wollsching-Strobel M; Majorski D; Berger MP; Schumacher F; Holle JF; Windisch W; Zimmermann M (International Journal of COPD)
Simon Koschel,1,2,* Sarah Bettina Stanzel,1,2,* Doreen Kroppen,1,2 Marieke Duiverman,3,4 Maximilian Wollsching-Strobel,1,2 Daniel Majorski,1,2 Melanie Patricia Berger,1,2 Falk Schumacher,2,5 Johannes Fabian Holle,2,6 Wolfram Windisch,1,2 Maximilian Zimmermann1,2 1Cologne Merheim Hospital, Department of Pneumology, Kliniken der Stadt Köln gGmbH, Cologne, Germany; 2Witten/Herdecke University, Witten, Germany; 3Department of Pulmonary Diseases and Home Mechanical Ventilation, University of Groningen, University Medical Center Groningen, Groningen, The Netherlands; 4Groningen Research Institute of Asthma and COPD (GRIAC), University of Groningen, Groningen, The Netherlands; 5Department of Rheumatology, Krankenhaus Porz Am Rhein, Cologne, Germany; 6Cologne Merheim Hospital, Department of Neurology, Kliniken der Stadt Köln gGmbH, Cologne, Germany*These authors contributed equally to this workCorrespondence: Maximilian Zimmermann, Department of Pneumology, Cologne Merheim Hospital; Kliniken der Stadt Köln gGmbH, Witten/Herdecke University, Faculty of Health/School of Medicine, Ostmerheimer Strasse 200, Köln, D-51109, Germany, Tel +49221890713468, Fax +4922189073666, Email zimmermannma@kliniken-koeln.deBackground: Non-invasive ventilation (NIV) is vital for managing chronic hypercapnic respiratory failure in COPD patients, yet the impact of handling issues like mask compliance triggering hospitalisations is often underestimated.Methods: A prospective, monocentric observational study was performed in COPD patients hospitalized for acute exacerbation with established home NIV therapy. Various questionnaires (CAT, SRI, BORG) and blood gas analysis were used to determine the severity and cause of respiratory insufficiency.Results: 59 patients (mean age 66.57 years ± 9.42, mean BMI 26.99 ± 8.63) were included. 54.24% were female (n=32). The overall cohort had a mean exacerbation rate of 2.24 ± 1.48 within the last 12 months prior to admission. Patients were divided into 4 sub cohorts based on their exacerbation trigger: infection (n=25), handling problem (n=12), non-infection (n=8), and an overlap cohort with evidence of both handling problem and non-handling problem (n=14). Significant differences exist when comparing exacerbation rate (handling-issue cohort: 2.58 ± 1.68 vs infection cohort: 1.76 ± 1.13, p=0.043), total hospital stay (handling-issue cohort: 9.25 ± 5.94 days vs infection cohort: 12.96 ± 5.76 days, p=0.039). There was no significant difference in health-related quality of life measured by the SRI (Summary Score 40.6± 12.3 vs 46.8± 14.2; p=0.103).Discussion: In our study, we were able to show that handling problems are associated with frequent exacerbations, cause long hospitalisation periods and are associated with a reduced aspects of quality of life. Patient education and training should therefore play a key role in the treatment of patients.Keywords: COPD, NIV, hospital admission, handling problems, adherence, hypercapnic respiratory failure